Supporting open plurilateral negotiations for multilateral liberalisation of trade - Anwarul Hoda (Indian Council for Research on International Economic Relations (ICRIER), 2023)
For many years now, lack of progress in multilateral trade negotiations has been a major cause of concern among WTO members. With diversity in the economic situation of members and differences in their stages of development, delay in concluding trade agreements is inevitable. However, the negotiating process has also been an obstacle to progress. All decisions must be taken by consensus and the full membership must be involved at every stage. Decision making by consensus is a legacy from the GATT 1947 days and is difficult, if not impossible, to change. Developing countries are strongly attached to the requirement as they consider it an important safeguard against the imposition of new obligations on them against their will and interest. This study is about the alternative of open plurilateral agreements (OPAs) that has given hope of a solution to the problem of process in negotiations by sidestepping the requirement for a consensus. The paper gives a detailed account of the use of OPAs in the GATT 1947 era and of its revival under the WTO Agreement. It describes the various areas of the WTO Agreement in which OPAs can be successfully employed to make progress in liberalisation as well as in rule-making. It also contains a description of the way in which the results of plurilateral agreements can be assimilated in the architecture of the WTO Agreement. Support has been growing for OPAs but certain issues have also been raised. The paper includes a critical analysis of the objections as well.
Keywords: F13; F53; F55; 330; International Trade Agreement; GATT; WTO